Pembuatan Laporan Keuangan Berbasis SAK EMKM Pada Usaha Selai Nenas PKK Mandiri Kelurahan Tangkerang Barat, Kota Pekanbaru - Helly Aroza Siregar; Febdwi Suryani; Suharti Suharti (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The purpose of implementing this community service is to produce a financial report in accordance with SAK EMKM. The service is carried out at the Usaha Selai Nenas PKK Mandiri Kelurahan Tangkerang Barat, where this business is a micro-scale business run by PKK’s women who want to improve the financial welfare for their families. The methods of implementing community services are observation, interviews, education and implementation. The results obtained are the availability of financial reports in accordance with SAK EMKM, namely Statements of Financial Position, Profit and Loss Reports and Notes to Financial Statements.